Effect of variation of normal force on seismic performance of resilient sliding isolation systems in highway bridges. - Iemura, Hirokazu (Earthquake engineering & structural dynamics.)
In this study, a series of shaking table tests are carried out on scaled models of two seismically isolated highway bridges to investigate the effect of rocking motion and vertical acceleration on seismic performance of resilient sliding isolators. In addition, performance of RSi is compared with system having solely natural rubber bearings. Test results show that variation of normal force on sliders due to rocking effect and vertical acceleration makes no significant difference in response of RSI systems. In addition, analytical response of prototype isolated bridge and the model used in experiments is obtained analytically by using non-linear model for isolation systems. It is observed that for seismically isolated bridges, dynamic response of full scale complex structures can be predicted with acceptable accuracy by experiments using a simple model of the structure.